Studies on activities of PTA, AK, ICL and MS enzymes involved in the acetate metabolism of Corynebacterium glutamicum - RUAN Hong; XUAN Ri-rong (浙江大学学报. 农业与生命科学版)
The four enzymes of acetate kinase (AK), phosphotransacetylase (PTA), isocitrate lyase (ICL) and malate systhase (MS) which are involved in the acetate metabolism of Corynebacterium glutamicum have been developed in their assay methods. The enzyme activities of AK, PTA, ICL and MS are analyzed comparatively while C. glutamicum grows on glucose or/and on acetate. The results showed there was “glucose effect” in carbon metabolism and acetate could significantly promote the induction of specific activities of acetate kinase, phosphotransacetylase, isocitrate lyase and malate systhase.